PENGARUH DIGITAL MARKETING TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE PADA PENJUALAN PERHIASAN SARI DEWI GOLD & SILVER - Pande Putu Yudhist Devananda; Ketut Elly Sutrisni (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
The development of digital technology has transformed traditional marketing paradigms into more interactive and measurable digital-based strategies. This study aims to analyze the effect of digital marketing on purchase intention with brand image as a mediating variable in the jewelry sales of Sari Dewi Gold & Silver in Gianyar, Bali. A quantitative approach was employed using primary data collected through questionnaires distributed to 141 respondents who had purchased or were potential buyers of the jewelry products. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that digital marketing has a positive and significant effect on both brand image and purchase intention, while brand image also has a positive and significant effect on purchase intention and mediates the relationship between digital marketing and purchase intention. These findings emphasize that effective digital marketing strategies not only directly enhance consumers’ purchase intentions but also strengthen brand image as a key factor in building consumer trust, providing both theoretical and practical implications for jewelry businesses to optimize digital marketing strategies in improving competitiveness.